Influence of Physical Self-Concept and Motivational Processes on Moderate-to-Vigorous Physical Activity of Adolescents - Núñez, Juan L.; Leon, Jaime; Valero-Valenzuela, Alfonso; Conte, Luis; Moreno-Murcia, Juan A.; Huéscar, Elisa (Frontiers in Psychology, 2021)
There is growing concern about the increasing decline in physical activity among adolescents. In the search for variables that may be related to physical activity, this study examined the influence of physical self-concept on objectively-measured moderate-to-vigorous physical activity (MVPA) of adolescents through the mediation of needs satisfaction and two types of autonomous motivation, for academic and for physical education. Data were collected from 618 students (301 boys and 317 girls) aged 10-14 years from 24 secondary schools in Spain. Path analysis results showed that physical self-concept positively predicted the needs satisfaction and this, in turn, was positively and significantly related to the two types of autonomous motivation. Finally, only the autonomous motivation for physical education significantly and positively predicted, and objectively measured MVPA of adolescents. Our findings showed that there was no evidence of an indirect effect of physical self-concept on MVPA. The results are discussed along the lines of the self-determination theory, by the analysis of the role of physical self-concept in increasing adolescents' physical activity.